Rare Histological Type of Adenoma of the Nonpigmented Ciliary Epithelium - Ishiahara, Kentaro (Case Rep Ophthalmol, 2019)
We report the rare case of an adenoma of the nonpigmented ciliary epithelium (NPCE). A 67-year-old healthy man presented with a regularly shaped and nonpigmented mass at the iris root of his right eye. His best-corrected visual acuity was 1.5 with normal intraocular pressure. During observation, the size of the tumor remained stable for 1.5 years but then rapidly grew, extending through the iris, and gradually enlarged to the point of compressing the iris. Ultimately, an iridocyclectomy with scleral resection under a lamellar scleral flap was performed. The histopathologic features of the resected tissue were consistent with adenoma of the NPCE. Histopathological analysis showed that the tumor consisted of both tubular and solid components. There were solid lesions inside of the ciliary epithelium and tubular lesions outside. We observed positive immunoreactivity to vimentin and cytokeratin CK (AE1/AE3) and negative reactivity to S-100 and CD68, both rarely associated with adenoma of NPCE. During 1 year of follow-up after the iridocyclectomy, no signs of tumor recurrence were observed.